A daily fever curve for the Swiss economy - Marc Burri; Daniel Kaufmann (Swiss Journal of Economics and Statistics, 2020)
Because macroeconomic data is published with a substantial delay, assessing the health of the economy during the rapidly evolving COVID-19 crisis is challenging. We develop a fever curve for the Swiss economy using publicly available daily financial market and news data. The indicator can be computed with a delay of 1 day. Moreover, it is highly correlated with macroeconomic data and survey indicators of Swiss economic activity. Therefore, it provides timely and reliable warning signals if the health of the economy takes a turn for the worse.
Keywords: 330; COVID-19; Composite leading indicator; Financial market data; News sentiment; Switzerland